Portable Water Heater Design with Battery Based Temperature Control: Desain Pemanas Air Portabel dengan Pengatur Suhu Bertenaga Baterai - Ilham Amrullah; Izza Anshory (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Portable heating devices are increasingly needed to support human activities in cold environments and emergency conditions. Specific Background Conventional water heating methods are limited by dependency on external power sources and lack flexibility for mobile use. Knowledge Gap Existing solutions have not fully addressed portability and independent power usage in compact heating systems for emergency response situations. Aims This study aims to design and develop a portable water heater using a battery-based system and digital thermostat control. Results The developed system utilizes an XH-W1209 thermostat and lithium battery, achieving water heating performance where 100 ml requires 5 minutes and 500 ml requires 25 minutes, with battery capacity decreasing by 10% every 5 minutes of operation. Novelty The integration of a thermos-based container with a battery-powered heating system enables standalone operation without direct electrical connection. Implications The device provides a practical solution for mobile water heating, supporting emergency handling such as hypothermia first aid and enabling flexible use in outdoor conditions. Keywords: Portable Heater, Water Heating System, Lithium Battery, Temperature Control, Thermostat Key Findings Highlights Heating duration increases proportionally with liquid volume Energy consumption shows consistent reduction during operation Automatic control maintains stable temperature conditions